The geographic problem in cephalopod genomics - Vecchione, Michael; Sweeney, Michael J.; Rothman, Paula L. (Frontiers in Marine Science, 2022)
Publications describing genomes of various cephalopod species have recently proliferated. Some papers have involved large geographic distances between the collection locality of sequenced specimens and the type locality of the presumed species. However, cryptic species have been demonstrated in many cephalopods. Therefore, even if the sequenced specimen is very similar morphologically to the species in question, the likelihood that it is a member of the species in question decreases with increasing distance from the type locality. An associated problem is that many publications do not provide information adequate to determine the source locality for the genomic sequence. We reviewed a decade of literature on mitochondrial genomes of cephalopods and found a total of 43 publications containing 48 species within 23 genera. Of the 48 species, only 17 could be evaluated for our geographic question. Distances between sampling locality and type locality of the named species ranged from 0 nautical miles (sampled at type locality) to half-way around the world. Where data were present for distance calculation, the average for the 17 species was 3785 km (2044 nmi).